2013
DOI: 10.1177/0004944113495500
|View full text |Cite
|
Sign up to set email alerts
|

Why poor children are more likely to become poor readers: The school years

Abstract: Socioeconomic status at the individual-and school-level are positively related to literacy achievement in all English-speaking countries. The components of socioeconomic statusincome, parent education and parent occupation -are each statistically significant predictors of school literacy achievement but they are primarily a proxy for more directly salient factors. This literature review outlines the factors that are most strongly implicated in literacy achievement. At the individual-level, they are early liter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
84
1
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(103 citation statements)
references
References 127 publications
(159 reference statements)
2
84
1
5
Order By: Relevance
“…In another study [7] it argued that by and large, students with higher socioeconomic status are those who have access to the best resources in their education. Other relevant studies found that socioeconomic status has an impact on academic outcomes [8], level of math and reading achievement [9], literacy achievement in all English-speaking countries [10], and help-seeking strategies of children [11].…”
Section: Objectives Of the Studymentioning
confidence: 99%
“…In another study [7] it argued that by and large, students with higher socioeconomic status are those who have access to the best resources in their education. Other relevant studies found that socioeconomic status has an impact on academic outcomes [8], level of math and reading achievement [9], literacy achievement in all English-speaking countries [10], and help-seeking strategies of children [11].…”
Section: Objectives Of the Studymentioning
confidence: 99%
“…They also note that, "A socioeconomic gradient to child health has been found in numerous studies; child health scores decline with SES." And, "The AEDI [Australian Early Development Index] shows that the proportion of children assessed as developmentally vulnerable on the 'emotional maturity' domain (which includes sociability, anxiety, aggression, hyperactivity and inattention) increased as SES decreased," (Buckingham, Wheldall, & Beaman-Wheldall, 2013). Low SES is linked to poor literacy, poor health, and behavior problems.…”
Section: Literature Reviewmentioning
confidence: 99%
“…OUTDOOR TIME IN PORTLAND ELEMENTARY SCHOOLS Although outdoor time enhances positive child development, low socioeconomic status (SES) does the opposite. Low SES is linked to poor literacy, poor health, and behavior problems (Buckingham, Wheldall, & Beaman-Wheldall, 2013). Based on the evidence that nature has a positive effect on health and behavior, children of lower SES may benefit from more time outdoors.…”
Section: Introductionmentioning
confidence: 99%
“…Predicting risk of literacy difficulties may be particularly challenging for teachers working in a low-income environment, given that poverty itself is a risk factor for slower acquisition of literacy (Buckingham, Bearman, & Wheldall, 2014;Hecht, Burgess, Torgesen, Wagner, & Rashotte, 2000). However, Hecht and Greenfield (2001) provide evidence that teachers remain accurate in a low socioeconomic status (SES) context.…”
mentioning
confidence: 99%